2018
DOI: 10.1177/0300985818789483
|View full text |Cite|
|
Sign up to set email alerts
|

Tropical Keratopathy (Florida Spots) in Cats

Abstract: The authors used microscopy and synchrotron-based small-angle X-ray scattering analysis (SAXS) to describe lesions macroscopically typical of tropical keratopathy ("Florida spots") from 6 cats on St Kitts. Microscopically, there were varying degrees of epithelial hyperplasia and thinning of the cornea (by 4% to 18%) due to loss of corneal stroma associated with dense accumulations of collagen in the superficial stroma. The collagen fibrils in lesions were wider and had more variable diameters (39.5 ± 5.0 nm, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
4
15
0
Order By: Relevance
“…This cat was evaluated in the same manner as other patients with corneal deposits, beginning with slit‐lamp examination and general laboratory tests, and then with further corneal OCT scan. This workup allows for the evaluation of other possible etiologies such as tropical keratopathy (“Florida spots”), and infectious crystalline keratopathy 16,17 . Although these two diagnoses were considered, the absence of an inciting event for tropical keratopathy, such as travel to a tropical area or fire ant exposure, along with a lack of distinctive lesions, allowed for exclusion of this etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cat was evaluated in the same manner as other patients with corneal deposits, beginning with slit‐lamp examination and general laboratory tests, and then with further corneal OCT scan. This workup allows for the evaluation of other possible etiologies such as tropical keratopathy (“Florida spots”), and infectious crystalline keratopathy 16,17 . Although these two diagnoses were considered, the absence of an inciting event for tropical keratopathy, such as travel to a tropical area or fire ant exposure, along with a lack of distinctive lesions, allowed for exclusion of this etiology.…”
Section: Discussionmentioning
confidence: 99%
“…This workup allows for the evaluation of other possible etiologies such as tropical keratopathy ("Florida spots"), and infectious crystalline keratopathy. 16,17 Although these two diagnoses were considered, the absence of an inciting event for tropical keratopathy, such as travel to a tropical area or fire ant exposure, along with a lack of distinctive lesions, allowed for exclusion of this etiology. The lesions present in tropical keratopathy are also white or cream-colored, but they usually have blurry cotton-like contours, unlike the welldefined lesions present in this feline patient.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 28 conducted in St. Kitts involving six domestic short‐haired cats demonstrated that tropical keratopathy is associated with alterations in the diameter and alignment of collagen fibers. The changes were detected by comparing the collagen supraorganization in the lesions to those in a control group, which included adjacent transparent corneal tissue and tissue samples collected from two clinically normal cats.…”
Section: Introductionmentioning
confidence: 99%
“…The technique has been used for the analysis of a wide range of substances, including biological materials where it has been particularly useful in studies of collagen in leather, (5)(6)(7)(8) tendon, (9,10) and the cornea, (11)(12)(13)(14)(15)(16)(17) most recently to characterize a lesion of veterinary importance. (18) The ultrastructure of collagen is often determined by electron microscopy, but to produce the thin tissue sections that are studied, tissues must rst undergo chemical preservation, also called xation. This prevents degradation of tissues by autolysis and putrefaction, stabilizes the ultrastructure, and introduces structural rigidity that facilitates sectioning.…”
Section: Introductionmentioning
confidence: 99%